BODY SHAMING IN MOVIES: A CASE STUDY ON SELECTED MOVIES - H, Harsha .; Joseph, Kelia; Devassy, Mariya; Sreena (International Journal of Psychosocial Rehabilitation, 2020)
–This paper aims to examine the potential influence of movies, in support and reflection of body shaming among women in the society. Body shaming happens in many ways; it is criticising or judging someone’s appearance or comment on their body and comparing it to other individuals. Women are always the major victims of body shaming. Female body-shaming is discussed in movies as an important element nowadays. Females always get conscious and influenced by their body, size, and colour. It’s becoming a normal process that one fat girl or dark-skinned will get bullied by others in society. She has to be shameful about what she is. Films are considered as the reflection of society and vice-versa. It influences people’s attitude as a whole and one to others. Body shaming has different perspectives in different cultures. This research is focusing on how movies indulge with body-shaming in different ways. For instance, comparing the Indian and the American culture, one can observe that body shaming happens in a repulsive way may be with different means. This paper intends to know how female body-size, colour etc. are portrayed in films. The paper attempts to analyse two selected movies from two different cultures; Dumplin’(2018), Thamaasha(2019). It relies on the social stigma of ‘body image’ and the effects on the society where the concepts of gender, race, and sexuality play a vital role.